A Branch and Bound Approach for Large Pre-Marshalling Problems - Tanaka, Shunji; Tierney, Kevin; Parreño-Torres, Consuelo; Alvarez-Valdes, Ramon; Ruiz, Rubén (European Journal of Operational Research)

Hyper-Reactive Tabu Search for MaxSAT - Ansótegui, Carlos; Heymann, Britta; Pon, Josep; Sellmann, Meinolf; Tierney, Kevin (Learning and Intelligent Optimization)

Specifying Web Interfaces for Command-line Applications Based on OpenAPI - Wolters, Dennis; Kirchhoff, Jonas; Engels, Gregor (Service-Oriented Computing – ICSOC 2019 Workshops)

Diffusion of Methane in Supercritical Carbon Dioxide Across the Widom Line - Guevara-Carrion, Gabriela; Ancherbak, Sergiy; Mialdun, Aliaksandr; Vrabec, Jadran; Shevtsova, Valentina (Scientific Reports)

All-neural Online Source Separation, Counting, and Diarization for Meeting Analysis - von Neumann, Thilo; Kinoshita, Keisuke; Delcroix, Marc; Araki, Shoko; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2019, Brighton, UK)
Automatic meeting analysis comprises the tasks of speaker counting, speaker diarization, and the separation of overlapped speech, followed by automatic speech recognition. This all has to be carried out on arbitrarily long sessions and, ideally, in an online or block-online manner. While significant progress has been made on individual tasks, this paper presents for the first time an all-neural approach to simultaneous speaker counting, diarization and source separation. The NN-based estimator operates in a block-online fashion and tracks speakers even if they remain silent for a number of time blocks, thus learning a stable output order for the separated sources. The neural network is recurrent over time as well as over the number of sources. The simulation experiments show that state of the art separation performance is achieved, while at the same time delivering good diarization and source counting results. It even generalizes well to an unseen large number of blocks.

Diffusion Limited Evaporation of a Binary Liquid Film - Chatwell, René Spencer; Heinen, Matthias; Vrabec, Jadran (International Journal of Heat and Mass Transfer)

Kirkwood-Buff Integration: A Promising Route to Entropic Properties? - Fingerhut, Robin; Vrabec, Jadran (Fluid Phase Equilibria)

Four‐Wave Mixing Holographic Multiplexing Based on Nonlinear Metasurfaces - Lin, Zemeng; Huang, Lingling; Xu, Zhen Tao; Li, Xiaowei; Zentgraf, Thomas; Wang, Yongtian (Advanced Optical Materials)

"Producing Cloud-Native": Smart Manufacturing Use Cases on Kubernetes - Schneider, Stefan Balthasar; Peuster, Manuel; Hannemann, Kai; Behnke, Daniel; Müller, Marcel; Bök, Patrick-Benjamin; Karl, Holger (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN) Demo Track)
Building on 5G and network function virtualization (NFV), smart manufacturing has the potential to drastically increase productivity, reduce cost, and introduce novel, flexible manufacturing services. Current work mostly focuses on high-level scenarios or emulation-based prototype deployments. Extending our previous work, we showcase one of the first cloud-native 5G verticals focusing on the deployment of smart manufacturing use cases on production infrastructure. In particular, we use the 5GTANGO service platform to deploy our developed network services on Kubernetes. For this demo, we implemented a series of cloud-native virtualized network functions (VNFs) and created suitable service descriptors. Their light-weight, stateless deployment on Kubernetes enables quick instantiation, scalability, and robustness.
Keywords: 5G; NFV; Smart Manufacturing; Cloud-Native; Kubernetes

Investigation of Near-Surface Defects of Nanodiamonds by High-Frequency EPR and DFT Calculation - Cho, F. H.; Peng, Z.; Biktagirov, T.; Gerstmann, Uwe; Takahashi, S. (The Journal of Chemical Physics)

Proton Irradiation Induced Defects in β-Ga2O3: A Combined EPR and Theory Study - von Bardeleben, Hans Jürgen; Zhou, Shengqiang; Gerstmann, Uwe; Skachkov, Dmitry; Lambrecht, Walter R. L.; Ho, Quoc Duy; Deák, Peter (APL Materials)

Methode zur Erfassung von Stofftransport an fluiden Phasengrenzflächen - Schulz, Andreas; Wecker, Christian; Kenig, Eugeny (Chemie Ingenieur Technik)

Ein Finite-Volumen Ansatz für den Stoffübergang an bewegten Phasengrenzflächen - Schulz, Andreas; Wecker, Christian; Kenig, Eugeny

Numerische Untersuchungen zum Stofftransport und Fluidmechanik bei der Tropfenbildung - Wecker, Christian; Schulz, Andreas; Heine, Jens; Bart, Hans-Joerg; Kenig, Eugeny

Visualization of Marangoni Phenomena during Droplet Formation - Heine, Jens; Wecker, Christian; Kenig, Eugeny; Bart, Hans-Joerg

In-situ Messung des Stofftransports bei der Tropfenbildung - Heine, Jens; Wecker, Christian; Kenig, Eugeny; Bart, Hans-Joerg

Stofftransport und Fluidmechanik bei der Tropfenbildung unter Berücksichtigung von Marangonikonvektion mittels CFD - Wecker, Christian; Schulz, Andreas; Heine, Jens; Bart, Hans-Joerg; Kenig, Eugeny

Stofftransport bei der Tropfenbildung - Heine, Jens; Wecker, Christian; Kenig, Eugeny; Bart, Hans-Joerg

Reduktion von parasitären Strömungen in Mehrphasensimulationen durch Verwendung der Height-Function Methode - Zibart, Alexander; Kenig, Eugeny

"A possibilistic finite element method for sparse data" - Dridger, A.; Caylak, I.; Mahnken, R.; Penner, E. (Safety and Reliability)